Corporate Security in the Asia-Pacific Region : Crisis, Crime, Fraud, and Misconduct. - Cubbage, CPP Christopher J. (Taylor and Francis, 2012)
As corporations and governments become more litigious and risk averse, international risk management becomes more complex. Corporate Security in the Asia-Pacific Region: Crisis, Crime, Fraud, and Misconduct examines real cases of corporate crisis, crime, fraud, and other misconduct that corporate security professionals need to be aware of to effectively protect people, operations, and assets within the region. Current security threats and risks are addressed to help readers conduct an informed risk assessment and analysis of operational risk. Providing detailed guidance on how to address the un.